พระบาทสมเด็จพระจุลจอมเกล้าเจ้าอยู่หัวกับกลุ่มศิลปินชาวฟลอเรนซ์ - หนึ่งฤดี โลหผล (คณะอักษรศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 1999)
During the visits of King Chulalongkorn to Italy in 1897 and 1907, many Florentine artists were contacted by his Majesty for different purposes. Edoardo Gelli and Michele Gordogiani painted royal portraits in Florence. Galileo Chini, a leading exponent of Italian Art Nouveau, was invited later to decorate the seven domes at Anantasamakhom Throne Hall in Bangkok. This relation between Siamese court and Florentine artists played an important role in the renovation of Siam particularly in the architectural and artistic point of view.